PENGARUH BULLYING SISWA SEKOLAH MENENGAH PERTAMA TERHADAP KESEHATAN MENTAL DI SMP MUHAMMADIYAH 07 MEDAN - Nurul Adela; Firman; Netrawati (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to determine the improvement in mental health from the impact of bullying by using individual services through a client-centred approach on seventh-grade students at SMP Muhammadiyah 07 Medan in the 2025/2026 academic year. Issues observed at the school indicate that many students struggle with self-control, such as frequently arriving late to school, inability to self-regulate, and being victims of bullying—both physical and psychological—leading to students becoming withdrawn and lacking self-confidence. The Client-Centred approach is employed to assist students in determining how to cope with reality and develop their personalities holistically, enabling them to resolve issues independently. This study employs observation and interview methods with four seventh-grade students collaborating with guidance and counselling teachers. The data analysis techniques used were data reduction, data presentation, and decision-making. The results of the study showed an improvement in students' mental health after receiving individual counselling services using the Client-Centred Approach. This study is expected to provide input to schools and guidance and counselling teachers in handling bullying cases and improving students' mental health in the school environment.